Hindī sāhitya kī paramparā, athavā, Hindī sāhitya kā ālocanātmaka itihāsa - Agravāla, Haṃsarāja, 1906- (SAMP early 20th-century Indian books project, 1950)
History of Hindi literature, from earliest times to date.